(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to evaluate the surface hardness and depth of cure of resin composites cured with a quartz tungsten halogen (QTH) lamp or a light emitting diodes (LED) unit. Swiss Tec (colten/whaledent AG, Switzerland) resin composite was placed in1, 2, 3, and 4 mm depth and 8 mm width metallic molds and cured using the QTH light or the LED unit for 40s. A total of 40 samples were made that divided into two groups according to the type of curing light with 20 samples each. Each group was subdivided into 4 groups according to the height of the mold with 5 samples each. Microhardness measurements were performed using a calibrated Vickers indenter (100 g load and 30s dwell time). Measurement of depth of cure was carried out by means of hardness ratio (bottom/top × 100). Results were analyzed by paired student’s t-tests (P < 0.05). Results showed that LED exhibited higher microhardness values than QTH unit and the difference was statistically significant (P = 0.03) at the top surface and highly significant (P = 0.001) at the bottom surface. Further more the results revealed that LED produced samples with hardness ratio (depth of cure) higher than QTH unit and the difference was highly significant (P = 0.004) at 3 mm depth. Both curing lights inadequately cure samples at 4 mm depth. Conclusions: Curing effectiveness of resin composite is better with LED than QTH unit especially when the composite thickness exceed 2 mm.